Development of an indoor GPS free self-positioning system for Mobile Ad Hoc Network (MANET) - A. Latiff, Liza (Penerbit UTM, 2008)
Position location (PL) has been an important and motivating criterion in position-based routing protocols which will reduce routing overhead. Several PL technologies such as Global Positioning System (GPS), the active badge system, the bat system and the cricket compass system have been proposed. GPS technology is very useful outdoor but quite ineffective indoors because walls in buildings block GPS transmissions. Other systems mentioned above are hardware-based which require additional devices for signal transmission and this will significantly incur additional cost of installation and maintenance. In this paper, the development of a GPS-free, simple self-positioning system to be implemented in MANET are presented where the node itself determines its location from hello message signals received that are being broadcast at intervals from specifically identified stationary nodes. Location of all nodes will be based on a global coordinate system which will provide a simpler routing task in any position-based routing protocol. The proposed system will be economically developed since the hardware required are laptops or PDAs with a standard IEEE 802.11 wireless LAN card which will have a relative large transmission coverage compared to Bluetooth and infrared signals.